Design and Analysis of the Mechanical Behaviour of Adhesively-Bonded CFRP T-Joints - Cardoso, João Manuel Vieira (2018)
Adhesively bonded joints have been increasingly applied in primary aerostructures, mainly due to their numerous advantages over mechanically fastened joints. More specifically, bonded Tjoints made from carbon fibre reinforced plastics (CFRPs) are commonly found as stiffening members on wing paneis and fuselage sections. Despite the well-known advantages of composites, aluminium stiffeners can yet be considered a safer and more conservative solution, since composite T-joints face delamination problems that typically initiate at the central noodle of the stiffener - the part where the three arms of the stiffener come together - and propagate through the adhesive bondtine. [...]